Hidden barriers to international trade - Curzon, Gerard; Curzon, Virginia (London : Trade Policy Research Centre, 1970)
The book makes an analysis of protectionism vis a vis free trade, in the belief that real possibilities for attenuating non-tariff measures of protection if a free trade wind is induced to blow once more.
Includes bibliographical references.
osc 21/05/2018
Keywords: Non-tariff trade barriers